(untitled) (International relations and international law Journal, 2018)
Education is a key priority for all countries in Central Asia. Today, the education system having passed a long way of reforming to modernize, open to cooperation both within the region and with other countries. A special place in the international cooperation in Central Asia in the field of education occupies the European Union. The article shows that the majority of the Central Asian states are interested in promoting cooperation with the European Union and bringing their systems in line with developments in the field of higher education in Europe. We analyze the goals and objectives of the Education Initiative. The main attention is paid to coordination of the existing funding opportunities, development of programs within the Educational Initiative, to their implementation and funding mechanisms, and also complete approach to sector. On the basis of the carried analysis the conclusion is drawn that projects of the European Union are focused on the higher education that first of all shows interest of the EU in forming of the new generation of elite oriented to the European value system. Key words: Education Initiative, educational platform, European Union, Central Asia.